A monolateral pigmented lesion of the nipple. (1st December 2022) - Volontè, Martina; Barruscotti, Stefania; Feltri, Monica; Brazzelli, Valeria; Tomasini, Carlo Francesco; Vassallo, Camilla
Abstract: Pigmented mammary Paget's disease is a very rare variant of mammary Paget's disease linked to an underlying carcinoma in almost all cases. We present the case of a 62‐year‐old female patient who came to our attention for the evaluation of a monolateral asymptomatic pigmented lesion of the right nipple, which turned out to be a pigmented mammary Paget's disease unassociated to an underlying malignancy – an extremely rare entity only anecdotally reported in literature. The two main peculiarities of our patient's lesion, the importance of immunohistochemistry in the differential diagnosis and the theories on its pathogenesis are discussed. Further studies are necessary to establish the best treatment options. Click here for the corresponding questions to this CME article.